Arduino based gas leakage and temperature monitoring and control system - Adoyi Boniface; A.Y. Nasir; A. M. Hassan (Institute of Advanced Engineering and Science, 2020)
Gas leakage is a major problem with industrial sectors, residential premises and gas powered vehicles like CNG (Compressed Natural Gas) buses etc. One of the preventive methods to stop accidents associated with the gas leakage is to install a gas leakage detection device at vulnerable places. The aim of this project is to develop such a device that can automatically detect and control gas leakages and also monitor temperature in vulnerable areas. The system detects the leakage of the LPG (Liquefied Petroleum Gas) using a gas sensor and then also monitors the temperature using a temperature sensor. When the LPG concentration in the air exceeds a certain level, the gas sensor senses the gas leakage and the output of the sensor goes LOW, the system then opens the exit windows, and then uses the GSM to alert the person about the gas leakage via SMS. Also, when the temperature of the environment exceeds a certain limit, it then turns ON the LED (indicator) and make an alarm through the buzzer. An LCD (16x2) displays the current temperature and gas leakage status in degree Celsius and PPM respectively.